Simulation of 5G-based vehicle network using OMNeT++ and SUMO - Tham, Jia Jun (Nanyang Technological University, 2023)
Vehicular communication systems have recently become automated and intelligent with state-of-the-art traffic technology and information converging on transport infrastructure. To establish intelligent traffic systems, vehicular communication technology is an indispensable component. This project aims to develop a testbed for 5G-based vehicular communication systems using OMNet++, which is an object-oriented modular discrete event network simulation framework used to simulate wireless communication networks. To support the 5G feature, a 5G library for OMNet++, simu5G, is integrated into OMNet++. Furthermore, the communication system will be connected with SUMO, which is a road traffic simulator, to provide traffic information. And Veins will be used to connect OMNet++ and SUMO. The result of the project is to enable vehicles to transmit messages using 5G with other vehicles in the platoon or base stations when the vehicles are moving on the regional map. The testbed is use to simulate the vehicle behavior in the Jurong area.